Knowledge, Risk Perception and Practice Regarding Tuberculosis Transmission among Long Distance Bus Drivers in Addis Ababa, Ethiopia: A Cross Sectional Study - Gebrehiwot, Tsegaye Tewelde (Ethiop J Health Sci, 2017)
BACKGROUND: Window opening during bus transportation is recommended as a tuberculosis prevention strategy.Yet, drivers are affected by lack knowledge and risk perception of passengers and assistants. Boosting knowledge of and notifying the high risk of tuberculosis transmission for every passenger could be too costly. However, strategies targeting bus drivers as key agents unlike targeting all passengers might be less costly for window opening. METHOD: Data were collected from November 18/2014 to December 21/2014 in inter-region bus stations of Addis Ababa using cross sectional study design. Samples of 306 participants were selected using simple random sampling, and data were collected through face-to-face interview. Data were entered into Epi-data version 3.1 andanalyzed using IBM SPSS version 21. RESULT: From a sample of 306 bus drivers, 303 were interviewed. Nine in ten and nearly half of participants believed in the need for opening all windows and avoiding overcrowding of passengers as TB preventive measures respectively. Few bus drivers (7.3%) believed that bus drivers and their assistants could be at risk of tuberculosis. The majority (85.7%) of bus drivers opened side window the whole day without precondition. Hearing tuberculosis related information from radio was a promoting factor for tuberculosis preventive measures among bus drivers. CONCLUSION: Tuberculosis preventive practices and knowledge of bus drivers seempositive (opportunities), despite their low risk perception (challenge). Using the opportunity, further empowering bus drivers to persuade passengers and assistants to open all the rest of the windows is needed.